MORPHOLOGICAL INVESTIGATION OF AFFIXES IN IMAGINE DRAGONS LYRICS - Wulandari, Herlina; Al Fauzi, Fatih; Ismaili, Ismaili (E-Link Journal, 2023)
This study was implemented to analyze the form of affixes’ changes in three Imagine Dragons songs as a study source for intermediate English students. This study applied qualitative corpus analysis initially the data results are presented in tabular form. Indeed, presented a detailed description of the data found. This research used document analysis to collect data where documents were taken from electronic form specifically at the website address lirikterjemahan.id. The results of this study show 39 words that have an affixation process in three songs, 35 (89,7%) inflectional affixes, and 4 (10,3%) derivational affixes were found. First, inflectional affixes do not change the part of speech but change the grammatical function belonging to the suffix –s as plural, -es as plural, -‘s as possessive, -ing as progressive (continuous), and -ed as past. Second, derivational affixes that can change the part of speech belonging to noun suffixes change the word to a noun in the suffix –ness, -dom, -er, and adjective suffixes change the word to an adjective in the suffix -less.  Keywords: Morphology, Derivational affixes, Inflectional affixes, Song lyric